A citric acid/cysteine based bioadditive for plasticization and enhancing UV shielding of poly(vinyl chloride). Issue 2 (19th October 2021) - Duan, Xuejun; Chen, Heng; Liu, Huan; Chen, Ming; Chen, Shaojun; Gao, Jihua
Abstract: A new bioadditive for poly(vinyl chloride) (PVC), diethylhexyl thiazolopyridine dicarboxylate (BTD), was designed and synthesized by the esterification between 2‐ethylhexanol and thiazolopyridine dicarboxylic acid. The chemical structure of BTD was characterized by Fourier transform infrared spectroscopy and NMR. As a main plasticizer, BTD had higher plasticizing efficiency, thermal stability and migration resistance than dioctyl phthalate. Furthermore, due to the thiazolopyridine conjugated structure, BTD possessed strong ultraviolet (UV) absorption that endowed its plasticized PVC film with excellent UV shielding property. The biomass resource combined with the above high performances make BTD a very promising additive for PVC plasticization and anti‐UV application. © 2021 Society of Industrial Chemistry. Abstract : A bioadditive was synthesized by esterification between 2‐ethylhexanol and thiazolopyridine dicarboxylic acid, and it possessed dual functions of plasticization and enhanced UV shielding for poly(vinyl chloride).